Development and evaluation of an AI-based exergame training system for ice-hockey players: a randomized controlled trial - Sieber, N.; Walser, S.; Weber, T.; Gubler, R.; Badertscher, H.; Eggenberger, P. (Current Issues in Sport Science, 2025)
Introduction: Executive functions (EF) are crucial for team sports athletes to perform effectively on the field. Especially in open-skill sports, such as ice-hockey, soccer, or volleyball, adaptability and responding appropriately to rapidly changing external cues are critical (Koch & Krenn, 2021). EF are divided into the three core components cognitive flexibility, inhibition or interference control, and working memory (Diamond, 2013). Elite athletes perform better in EF tasks compared to non-elite athletes (Logan et al., 2023) and higher EF may predict future elite potential in young team sports athletes (Lundgren et al., 2016; Vestberg et al., 2012). Exergaming combines exercise and video gaming and couples cognitive and physical stimuli. This innovative training approach was effective in improving cognitive functioning, particularly EF, in younger and older populations (Chan et al., 2024; Eng et al., 2023), however, has rarely been investigated in athletes (Martin-Niedecken et al., 2020). The main goal of this study was to develop a novel ice-hockey specific exergame and gain insights into its effects on EF in competitive ice-hockey players. Secondary outcomes included lower limb neuromuscular performance as well as exergame acceptance, usability, feasibility (adherence), and training intensity. Increased EF and neuromuscular performance in the intervention group were hypothesized.